A physically-based constitutive model for a novel heat resistant martensitic steel under different cyclic loading modes: Microstructural strengthening mechanisms. (June 2023) - Song, Kai; Wang, Kaimeng; Zhao, Lei; Xu, Lianyong; Ma, Ninshu; Han, Yongdian; Hao, Kangda; Zhang, Libin; Gao, Yalin
Highlights: A physically-based model was proposed to simulate cyclic responses under fatigue and creep-fatigue condition. Four types of microstructural strengthening mechanisms were revealed. The dynamic processes when dislocation was blocked by hard and soft phases were simulated. A relationship between fatigue test and creep-fatigue test was established via dislocation density and dislocation motion. Abstract: Cyclic responses of a novel heat resistant martensitic steel, 9Cr3Co3W1CuVNbB steel, under different loading modes were studied to reveal its complex strengthening mechanisms at high temperature. Based on the experimental observations, dislocation strengthening, precipitation strengthening by M23 C6 phase, MX phase, and Cu-rich phase, and subgrain boundary strengthening were the main mechanisms for its excellent fatigue and creep-fatigue properties. In particular, the dynamic process of interaction between phase and dislocation were studied with the help of molecular dynamics method, and the different contributions of hard and soft phases in the studied steel were determined in fatigue and creep-fatigue loading. Based on these phenomena, a physically-based constitutive model was proposed for both fatigue and creep-fatigue (dwell fatigue at elevated temperature) tests considering various micromechanical mechanisms. Three ways for dislocation annihilation were proposed to simulate the dislocation evolution under different loadings. In addition, the effect of Cu-rich phase was modeled by critical breaking angle and dislocation line tension. The capability of the proposed model under different loading modes was verified by comparing cyclic responses, hysteresis loops, stress relaxation, and dislocation density evolution. The proposed model provides an alternative perspective on understanding fatigue and creep-fatigue behaviors of heat resistant martensitic steels owning the similar strengthening mechanisms.